(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
An electoral system is a set of rules governing how elections and referendums are conducted and their results determined. Current systems, such as ballot box voting or electronic voting, face numerous challenges, including security threats like DDoS attacks, vote manipulation, malware, and polling booth capturing. Additionally, they require extensive resources, paperwork, and time, leading to inefficiencies and public distrust. Hackable microchips or servers further exacerbate these vulnerabilities. Blockchain voting offers a transformative solution to these challenges. By utilizing a decentralized, peer-to-peer network, blockchain ensures security against DDoS attacks and eliminates centralized authority vulnerabilities. Citizens can conveniently cast their votes via personal devices after identity verification. Blockchain’s immutability ensures voting records are tamper-proof, easily verifiable, and transparent, with real-time vote tallying. This system significantly reduces costs, saves time, and enhances accessibility, paving the way for direct democracy. An E-Voting System Using Blockchain leverages blockchain’s core features, including decentralization, cryptographic encryption, and immutability, to modernize electoral processes. Smart contracts securely verify voter identities and record votes in a transparent and tamper-resistant manner. This system enhances security, reduces fraud, and bolsters public trust in elections, offering a novel and innovative approach to achieving secure and transparent digital voting in the future.